A review of the pharmacology of osmotic agents for the treatment of glaucoma in dogs - MAŚLANKA, T.; ZUŚKA-PROT, M. (Journal of the Hellenic Veterinary Medical Society, 2018)
At present, the only proven way to treat glaucoma is to lower intraocular pressure (IOP). Osmotic agents constitute an important class of ocular hypotensive agents. These medications are used for the rapid reduction of IOP, typically in emergency situations, in which IOP is severely elevated and there is a high risk of permanent and irreversible damage of the optic nerve. This paper summarizes the current state of knowledge on the mechanism of action of osmotic agents and their effect on IOP in dogs. Moreover, it discusses the possible undesirable side effects of these medications and presents the current ideas about their role and status in the medical management of canine glaucoma.